The Relationship Between Macroeconomics Variables and Islamic Stock Market Returns Listed in Indonesian Islamic Stock Index - Widyan Apriliska Fajri; Devita Alliv Nurdiana; Sulistya Rusgianto (Journal of Islamic Economics Lariba, 2020)
ABSTRACT:The aim of this paper is to explore the extent to which macroeconomic variables affect the Islamic stock market behavior in Indonesia between Oct 2014 until the end of 2019. The paper uses the latest estimation technique of Autoregressive Distributed Lag (ARDL) model approach to cointegration. The data used is secondary data by collecting data from the official websites of Bank Indonesia, BPS, IDX, and Indopremier. The results suggest that GDP, interbank interest rates, IHSG seem to be suitable targets for the government to focus on in short-term. As for long-term, the GDP and IHSG significantly influence the Islamic stock market return, and that's the targets for the government to focus in order to stabilize the Islamic stock market and to encourage more capital flows into the market.Keywords: Islam, Stock Market, Macroeconomics, Indonesia